Enhancing Critical Thinking through Shakespeare’s Sonnet 116: A Problem-Based Approach in a Cross-Cultural Middle School Classroom - Bendraou Rachid; Shih Yi-Huang; Sana Sakale; Taoufik Alaoui Hichami (Scientia Publica Media, 2025)
This study investigates how Shakespeare’s Sonnet 116 is used as a resource to encourage critical thinking among third-year middle school students in a multiculturally mixed classroom setting in Morocco. Twenty-five students were involved in a learning intervention in the PBL (problem-based learning) framework, with a focus on collaborative inquiry, cultural interpretation, and performance activities. A one-group pre-test/post-test design was used in this study to examine differences in the students’ critical thinking from prior to the intervention toward after the intervention. Findings suggested that students had learned to interpret literary topics, negotiate abstractions such as love or fidelity, and relate these to their real circumstances. Discussion and production outside of the sonnet had encouraged students to exercise their interpretive skills, and they had gained experience in cognition, argumentation, and reflection. The results provide evidence of the potential of embedding classics in contemporary pedagogy, such as PBL, to stimulate students’ cognitive engagement and promote intercultural understanding. The study also demonstrates the way Shakespeare’s works, if contextualized effectively, can overcome cultural frontiers and offer wider possible resources for literacy and critical understanding. The findings suggest that literature-based instruction can offer benefits beyond the development of academic literacy skills, in helping shape open-minded, reflective individuals who can engage in thoughtful exploration of diverse views. In the final analysis, the paper supports the pedagogical benefit of using Shakespeare in Moroccan schools and calls for both lovers of literature and lovers of education to tap into literature as a conduit for critical and culturally responsive pedagogy. These educational strategies enhance classroom conversation, foster interpretative independence, cultivate empathy, promote student agency, and stimulate profound engagement with many human experiences.